Could someone help me with this please?

Prove that k=1n1(nk)cos2kπn=n2\displaystyle\sum_{k=1}^{n-1}(n-k)\cos\frac{2k\pi}{n}=-\frac{n}{2} where n3n\ge3 is an integer.

#Algebra #ComplexNumbers #Trigonometry #Proofs

Note by Omkar Kulkarni
6 years, 3 months ago

No vote yet
1 vote

  Easy Math Editor

This discussion board is a place to discuss our Daily Challenges and the math and science related to those challenges. Explanations are more than just a solution — they should explain the steps and thinking strategies that you used to obtain the solution. Comments should further the discussion of math and science.

When posting on Brilliant:

  • Use the emojis to react to an explanation, whether you're congratulating a job well done , or just really confused .
  • Ask specific questions about the challenge or the steps in somebody's explanation. Well-posed questions can add a lot to the discussion, but posting "I don't understand!" doesn't help anyone.
  • Try to contribute something new to the discussion, whether it is an extension, generalization or other idea related to the challenge.
  • Stay on topic — we're all here to learn more about math and science, not to hear about your favorite get-rich-quick scheme or current world events.

MarkdownAppears as
*italics* or _italics_ italics
**bold** or __bold__ bold

- bulleted
- list

  • bulleted
  • list

1. numbered
2. list

  1. numbered
  2. list
Note: you must add a full line of space before and after lists for them to show up correctly
paragraph 1

paragraph 2

paragraph 1

paragraph 2

[example link](https://brilliant.org)example link
> This is a quote
This is a quote
    # I indented these lines
    # 4 spaces, and now they show
    # up as a code block.

    print "hello world"
# I indented these lines
# 4 spaces, and now they show
# up as a code block.

print "hello world"
MathAppears as
Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.
2 \times 3 2×3 2 \times 3
2^{34} 234 2^{34}
a_{i-1} ai1 a_{i-1}
\frac{2}{3} 23 \frac{2}{3}
\sqrt{2} 2 \sqrt{2}
\sum_{i=1}^3 i=13 \sum_{i=1}^3
\sin \theta sinθ \sin \theta
\boxed{123} 123 \boxed{123}

Comments

Definitely, you can approach it via @Incredible Mind's Method but I would like to share another method.

We can proceed by using Euler's Formula eix=cosx+isinxe^{ix} = \cos x + i\sin x cosx=eix+eix2\Rightarrow \cos x = \frac{e^{ix}+e^{-ix}}{2}

Thus, setting x=2kπnx= \frac{2k\pi}{n}, we can compute the sum as follows:

k=1n1(nk)cos2kπn=k=1n1(nk)ei2kπn+ei2kπn2=n2k=1n1(ei2kπn+ei2kπn)12k=1n1k(ei2kπn+ei2kπn)=n2k=1n1(ei2kπn+ei2kπn)12k=1n1k(ei2kπn+ei2kπn)\begin{aligned} \sum_{k=1}^{n-1} (n-k)\cos \frac{2k\pi}{n} & = & \sum_{k=1}^{n-1} (n-k) \frac{e^{i\frac{2k\pi}{n}}+e^{-i\frac{2k\pi}{n}}}{2} \\ & = & \frac{n}{2} \sum_{k=1}^{n-1} \left(e^{i\frac{2k\pi}{n}}+e^{-i\frac{2k\pi}{n}}\right) - \frac{1}{2} \sum_{k=1}^{n-1} k \left( e^{i\frac{2k\pi}{n}}+e^{-i\frac{2k\pi}{n}}\right) \\ & = & \frac{n}{2} \sum_{k=1}^{n-1} \left(e^{i\frac{2k\pi}{n}}+e^{-i\frac{2k\pi}{n}}\right) - \frac{1}{2} \sum_{k=1}^{n-1} k \left( e^{i\frac{2k\pi}{n}}+e^{-i\frac{2k\pi}{n}}\right) \\ \end{aligned} Now that above series (the first sum) is a simple Geometric Expansion and the second one can be obtained by differentiating the first one. (Hint : r=1nxr=x(xn1)x1\sum_{r=1}^{n} x^r = \frac{x(x^n-1)}{x-1} and r=1nrxr=x+(nxn1)xn+1(x1)2\sum_{r=1}^{n} rx^r = \frac{x+(nx-n-1)x^{n+1}}{(x-1)^2})

Finally, it evaluates to k=1n1(nk)cos2kπn=n2(2)12(n)=n2\sum_{k=1}^{n-1} (n-k)\cos \frac{2k\pi}{n} = \frac{n}{2}\left(-2\right)-\frac{1}{2}\left(-n\right) = -\frac{n}{2} (I urge the reader to verify the above result themselves)

EDIT : \textbf{EDIT : } A general approach for finding the sum of series of type k=1nkrk\sum_{k=1}^n kr^k (doesn't involves differentiation)

Let Sn=k=1nkrk=r+2r2+3r3++nrnS_n = \sum_{k=1}^n kr^k = r + 2r^2 + 3r^3 + \ldots + nr^n

Then observing closely

Sn=r+2r2+3r3++nrnrSn=r2+2r3++(n1)rn+nrn+1\begin{aligned} S_n & = & r + 2r^2 + 3r^3 + \ldots + nr^n \\ rS_n & = & \qquad r^2 + 2r^3 + \ldots + (n-1)r^n + nr^{n+1} \end{aligned}

Subtracting the second series from second one, we get

(1r)Sn=(r+r2+r3++rn)nrn+1=r(1rn)1rnrn+1(1-r)S_n = (r + r^2 + r^3 + \ldots + r^n) - nr^{n+1} = \frac{r(1-r^n)}{1-r}-nr^{n+1} Sn=r(1rn)(1r)2nrn+11r\Rightarrow S_n =\frac{r(1-r^n)}{(1-r)^2}-\frac{nr^{n+1}}{1-r}

I hope that helps :):)

Kishlaya Jaiswal - 6 years, 3 months ago

Log in to reply

Oh okay. Thanks!

Omkar Kulkarni - 6 years, 3 months ago

To distinguish the 2 approaches, you should explain that the second summation can be obtained by methods other than differentiation, especially since Omkar said he doesn't know differentiation.

This is a useful formula to be aware of, to sum scenarios like this.

Calvin Lin Staff - 6 years, 3 months ago

Log in to reply

ok sir, I'll edit my solution, right now. :):)

Kishlaya Jaiswal - 6 years, 3 months ago

split it .then 1st can be known by using complex numbers.2nd sum from differentiation of

S=sinx+sin2x+sin3x...sin(n-1)x.........use the sum formula .then diff. w.r.t x both sides.then sub x=2pi/n.

i cannot type because i dont know LATEX

incredible mind - 6 years, 3 months ago

Log in to reply

Oh okay, but I don't know about differentiation. Is there any other method? I think complex numbers come handy.

Omkar Kulkarni - 6 years, 3 months ago

Log in to reply

But there too you need to use differentiation.

Anyways, I'll definitely think of some another approach which doesn't involves differentiation.

Kishlaya Jaiswal - 6 years, 3 months ago
×

Problem Loading...

Note Loading...

Set Loading...